Degradation of circulating DNA by extracorporeal circulation over nuclease immobilized on nylon microcapsules. - Terman, D S (1976)
Studies were undertaken to determine whether deoxyribonuclease I, (DNase I) once immobilized on activated nylon microspheres, would be capable of degrading circulating DNA in vitro and in vivo in an extracorporeal circulation system in dogs. Nylon microspheres were prepared and after gentle hydrolysis and glutaraldehyde treatment, demonstrated a retention of up to 4.73 mg of Dnase I. In vitro studies showed that DNase I immobilized on microspheres degreded a significant percentage of 125I-native DNA (nDNA) within 15 min. Mongrel dogs were injected with 125I-nDNA and a variation in initial t 1/2 in individual animals was observed. Therefore, for experimental studies, 125I-nDNA was injected and decay was recorded during a control period in which untreated microcapsules were utilized in the extracorporeal system. DNase I microspheres were then introduced into the extracorporeal circuit which resulted in an acceleration of degradation of acid precipitable 125I-nDNA. When 200 mug of unlabeled DNA with 125I-nDNA was injected, a similar augmentation of DNA degradation was noted after extracorporeal circulation over DNase I microcapsules. This effect could not be attributed to release of DNase I from the microspheres since no 131I-DNase was detected in the serum or organs of the dogs at the conclusion of the experiments. 125I-nDNA:anti-DNA complexes were passively injected into dogs and after a similar control period of circulation over untreated microcapsules. DNase I microspheres were introduced. Results showed a rapid acceleration in the degradation rate of 125I-nDNA:anti-DNA complexes precipitable with (NH4)2SO4. Extracorporeal circulation over nylon microspheres resulted in no significant alteration of the host's hematocrit or platelet count, and little residual cellular debris on the microcapsules. These data suggest that DNAase immobilized on nylon microspheres may have a potential role in the specific therapy of systemic lupus erythematosus, when it is desirable to hydrolyze DNA circulating free or in combination with antibody.